Teori Roger Fowler dalam Strategi Penggunaan Kosakata dan Tata Bahasa pada Pemberitaan Lintaserayu.Com - Marhamah, Neneng Aam Siti (Sahabat Publikasi, 2024)
One topic of crime reporting and legal issues that is currently being widely discussed is murder cases. Critical discourse analysis helps uncover and understand hidden agenda interests behind the way reporting is done. By using Roger Fowler's critical discourse analysis approach, this research will pay attention to how the Lintasserayu.com mass media uses certain vocabulary, grammar and transformations to shape and direct readers' views. This type of research is descriptive qualitative research and tends to use analysis. Process and meaning (subject perspective) are more emphasized in qualitative research. From the results of the research analysis and discussion, there is the use of Roger Fowler's theory in the vocabulary aspect; limiting views, discourse battles, and marginalization, as well as grammatical aspects in the form of using active sentences in writing news headlines to reveal the father-in-law as the subject (S), the perpetrator of the murder as the party to blame. Fitria's victim is marginalized and leads readers to position themselves as those who share in the cruelty towards the victim by the perpetrator.